Radicalism of Islamic Politics: Metamorphosis of DI/TII (Darul Islam/Indonesia Islamic Army) in Olan Hamlet, Garut? - Khamami Zada (Mimbar Agama Budaya, 2023)
Radicalism of Islamic politics in Indonesia has been characterized with violence. In the context of DI/TII (Darul Islam/Indonesia Islamic Army), Islamic politics refers to the rebel movements against the Indonesian government in view of both political disappointment and radical religious understanding. This study aims to analyze the adaptation of DI/TII in Islamic education in Olan Hamlet, Garut as the basis of the DI/TII movement. It used a qualitative method based upon primary data obtained from interviews with the Head of Islamic Boarding School Nurul Falah in Olan Hamlet, Garut, community figures, religious figures nearby and government. This study found that the radical Islamic political movement of DI/TII did not undergo any metamorphosis to the Islamic education movements through the Madrasah and Islamic boarding school of Nurul Falah in Olan Hamlet, Garut. In fact, the Islamic boarding school and Madrasah have had some efforts to campaign for moderate religious understanding through the programs and curricula. Hence, there are no worries of government about the emergence of the radical movements in Olan Hamlet. The religious figures, however, still suspect the metamorphosis of DI/TII in this hamlet. Keyword: Radicalism, DI/TII, Islamic Politics